Preparation method of fluorescent nano-particles and fluorescent nano-particles prepared by same
Through self-assembly technology, the fluorescent molecules and non-conjugated polymers are fixed near the monomer molecules, which solves the fluorescence quenching problem of the fluorescence energy resonance transfer system during solid phase transformation, and achieves a stable FRET system and rapid release of fluorescent molecules.
Patent Information
- Application Number
- CN202311345952.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
AI Technical Summary
When the existing fluorescence energy resonance transfer system is transformed from liquid phase to solid phase, it is easy to cause fluorescence quenching due to interactions such as π-π stacking and destroy the FRET system.
By utilizing self-assembly technology, fluorescent molecules and non-conjugated polymers are immobilized near the motif molecules through non-covalent action, forming a stable FRET system.
It has achieved widespread applications in the fields of solid fluorescent materials and directed drug release, maintained the efficiency of fluorescent energy resonance transfer, and achieved rapid release of fluorescent molecules by destroying hydrogen bonds.
Smart Images

Figure CN119842391A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing fluorescent nanoparticles and the fluorescent nanoparticles prepared therefrom, and belongs to the field of fluorescent materials. Background Art
[0002] Fluorescence resonance energy transfer (FRET) was proposed in the 1930s and verified in experiments in the 1960s. After more than 100 years of development, it has been widely used in photosynthesis, optoelectronic devices, biodiagnosis and treatment, environmental monitoring and other fields. However, the design and development of fluorescence resonance energy transfer systems that can be applied to both solids and liquids is full of challenges. On the one hand, the design of intramolecular FRET systems based on traditional organic molecules is mostly based on electron transfer in the single-molecule state, and these organic molecules often have large conjugated systems. During the transition from liquid phase to solid phase, aggregation-induced fluorescence quenching will occur due to interactions such as π-π stacking, and the FRET system will be destroyed; on the other hand, methods based on surface modification molecules of fluorescent nanomaterials and fluorescent molecule pairs will also cause changes in parameters such as the spatial orientation angle and distance between the fluorescent energy donor and the acceptor due to phase transition, resulting in the disappearance of FRET or a significant reduction in efficiency.
[0003] Supramolecular self-assembly technology has brought a new solution to this problem. Self-assembly refers to the phenomenon and process in which building blocks such as small organic molecules, polymers, biomacromolecules and nanoparticles spontaneously form ordered structures under non-covalent interactions. The blocks are connected in an orderly manner through non-covalent bonds to form assemblies with specific structures or functions, which have shown great application potential in biology, chemistry, physics, medicine and other fields. Summary of the invention
[0004] By using self-assembly to construct nanoparticles, on the one hand, fluorescent molecules can be fixed near the basic molecules through non-covalent interactions, and then enter the interior of the self-assembled nanoparticles through the self-assembly process to form a relatively stable FRET system. On the other hand, when the intermolecular interaction driven by self-assembly disappears, the FRET energy donor and the ligand can be separated, allowing the fluorescent molecules to be dispersed into the required system, which has broad application prospects in the fields of solid fluorescent materials and directional drug release.
[0005] According to one aspect of the present application, a method for preparing fluorescent nanoparticles is provided, comprising the following steps:
[0006] The mixed solution containing the non-conjugated polymer, the fluorescent molecule and the solvent I is mixed with the solvent II to obtain the fluorescent nanoparticles.
[0007] The molecular weight of the non-conjugated polymer is 7000-15000Da;
[0008] The end-capping group of the non-conjugated polymer is a carboxyl group;
[0009] The non-conjugated polymer contains pendant carboxyl groups;
[0010] The non-conjugated polymer is obtained by the following method:
[0011] Mixing polycarboxylic acid and polyamine, reacting, and drying to obtain the non-conjugated dehydrated polymer;
[0012] The polycarboxylic acid is selected from at least one of oxalic acid, trisaccharic acid, succinic acid, 1,2,4-butanetricarboxylic acid, 1,2,3,4-butanetetracarboxylic acid, glutaric acid, adipic acid, and 1,2,4,5-cyclohexanetetracarboxylic acid;
[0013] The polyamine is selected from at least one of ethylenediamine, propanetriamine, 1,3-propylenediamine and phenylenediamine;
[0014] The reaction temperature is 80-260°C;
[0015] The reaction atmosphere is an inert gas atmosphere.
[0016] The molar ratio of the polycarboxylic acid to the polyamine is 1:10 to 10:1.
[0017] The reaction is a melt polymerization reaction.
[0018] The reaction time is 0.5 to 6 hours.
[0019] The inert gas atmosphere is selected from at least one of nitrogen, helium and argon.
[0020] Optionally, the molecular weight of the non-conjugated polymer is 1000-15000 Da.
[0021] Optionally, the non-conjugated polymer is selected from poly N-(3-phenyl)-2-carboxymethylamide-succinimide, poly N-ethyl-2-carboxymethylamide-succinimide, poly N-ethyl-2-carboxymethylimide-succinimide, polyphenyl oxalic acid diamide, polyethyl oxalic acid diamide, polyethyl oxalic acid diimide, polyethyl glutaric acid diamide, polyethyl glutaric acid diimide, polyphenyl glutaric acid diamide, polyphenyl glutaric acid diimide, polyethyl succinic acid diamide, polyethyl succinic acid diimide, polyphenyl succinic acid diamide, polyphenyl succinic acid diimide, polyphenyl oxalic acid diimide;
[0022] The fluorescent molecule is selected from at least one of fluorescein, rhodamine B, coumarin, platinum (II) MESO-tetrakis (pentafluorobenzene), proflavine hydrochloride, Nile red, (T-4)-[3-bromo-5-[(4-bromo-3,5-dimethyl-2H-pyrrole-2-ylidene-κN)benzyl]-2,4-dimethyl-1H-pyrrolidone-κN]difluoroboron (bromofluoroboron dipyrrole), cy3, terpyridine ruthenium chloride, 9,10-anthraquinone, and 2-methyl-7-quinolinamine;
[0023] The solvent I is selected from at least one of DMSO, methanol, ethanol, water, acetonitrile and acetone;
[0024] The mass ratio of the non-conjugated polymer to the fluorescent molecule is 1:0.01-1.
[0025] The mixed solution also contains monomers;
[0026] The monomer is selected from at least one of oxalic acid, trisaccharic acid, succinic acid, glutaric acid, ethylenediamine, and diaminobenzene;
[0027] The mass ratio of the non-conjugated polymer to the monomer is 1:0.01-10.
[0028] The solvent II is selected from at least one of ethanol, chloroform, acetone, acetonitrile, toluene and n-hexane;
[0029] The volume ratio of the mixed solution to the solvent II is 0.1 to 1:10.
[0030] The yield of the above method is 60-95%.
[0031] Specifically,
[0032] (1) a low molecular weight non-conjugated polymer having a self-assembly function, and at least one of a polymerizable monomer and a fluorescent molecule are uniformly dispersed in a solvent and uniformly stirred;
[0033] (2) gradually adding a second solvent until a low molecular weight non-conjugated polymer is precipitated and precipitated, filtering and drying the resulting precipitate, thereby obtaining releasable nanoparticles with intraparticle fluorescence energy resonance transfer;
[0034] (3) The obtained nanoparticles are dispersed in a DMSO solution, and then chloroalkane is added and shaken to separate the fluorescent molecules from the low molecular weight self-assembled non-conjugated polymer.
[0035] The order of addition in step (1) is: first add polyamide and polyimide and stir, then add fluorescent molecules and continue stirring; or first add polyamide and polyamidoamine, then add polymerization monomer and stir, and finally add fluorescent molecules and stir.
[0036] According to another aspect of the present application, there is provided a fluorescent nanoparticle prepared by the above-mentioned method for preparing the fluorescent nanoparticle.
[0037] Self-assembled non-conjugated polyamides and polyimides are self-assembled to induce blue fluorescence. Through the technical scheme in the present invention, fluorescent molecules can be gathered near the polymer chain through hydrogen bonds and van der Waals effects, and produce fluorescence energy resonance transfer with the amides / subamides of the excited state planar structure, so that the polymer self-assembled particles have the fluorescence characteristics of fluorescent molecules. If firstly a polymerization monomer is added in the particle, since the polymerization monomer (polycarboxylic acid or polyamine) can be adsorbed on the polymer by hydrogen bonding, when the fluorescent molecules are added again, the distance between the polymer and the fluorescent molecules is affected by the polymerization monomer concentration, and the fluorescence energy resonance transfer is cut off, so the fluorescence of the product simultaneously shows the duality of the fluorescence induced by the self-assembly of the polymer and the fluorescence of the internally embedded fluorescent molecules. On this principle basis, the intensity of this binary fluorescence can be adjusted by adjusting the monomer concentration. In addition, DMSO and chloroalkane can be effectively used to destroy the polymer self-assembly, polymerization monomer adsorption and fluorescent molecule adsorption that depend on hydrogen bonds, and then realize that the fluorescent molecules are released from nanoparticles.
[0038] The beneficial effects of this application include:
[0039] (1) The preparation method is simple, low cost, short cycle and high yield
[0040] (2) It is not restricted by the chemical structure of fluorescent molecules and any type of fluorescent molecules can be used.
[0041] (3) The fluorescent molecules can be quickly released from the self-assembled nanoparticles by breaking the hydrogen bonds without any other complicated operations. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is the nanoparticles in Example 1 1 H-NMR spectrum.
[0043] Figure 2a , b are electron microscope images of the nanoparticles in Example 1, wherein the scale of a is 10 nm and the scale of b is 5 nm.
[0044] Figure 3 This is the electron microscope image of the oligomer in Example 1, with a scale of 10 nm.
[0045] Figure 4 3D fluorescence spectrum of the oligomer in Example 1.
[0046] Figure 5 This is the three-dimensional fluorescence spectrum of the nanoparticles in Example 1.
[0047] Figure 6 The fluorescence spectra and photos of the supernatant and lower layer liquid after adding DMSO and dichloromethane in Example 1 are shown. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited thereto.
[0049] Example 1
[0050] 0.2 g of poly (N-(3-phenyl)-2-carboxymethylamide)-succinimide with an average molecular weight of 8000 Da was dissolved in 3 mL of dimethyl sulfoxide at room temperature and stirred evenly. Then 4 mg of rhodamine B was added and stirring was continued. Then 50 mL of methanol was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 75%.
[0051] 20 mg of poly (N-(3-phenyl)-2-carboxymethylamide-succinimide) doped with rhodamine B was dissolved in a mixed solution of DMSO and water in a volume ratio of 1:1, and then a dichloromethane solution with a total volume ratio of 0.1 was added. After shaking, the solution was separated into layers. Under ultraviolet light, the red fluorescent rhodamine B was in the lower layer of the three filters, while the blue fluorescent poly (N-(3-phenyl)-2-carboxymethylamide-succinimide) was in the upper layer.
[0052] Figure 1 is the nanoparticles in Example 1 1 H-NMR spectrum. It can be seen from the figure that rhodamine B is successfully loaded into the nanoparticles, and the hydrogen spectrum integration shows that the content is low.
[0053] Figure 2a , b are electron microscope images of the nanoparticles in Example 1, wherein the scale of a is 10 nm and the scale of b is 5 nm. It can be seen from the figure that the size of the nanoparticles assembled by rhodamine B and poly (N-(3-phenyl)-2-carboxymethylamide-succinimide) is between 40-50 nm.
[0054] Figure 3 This is the electron microscope spectrum of the oligomer in Example 1, with a scale of 10 nm. It can be seen from the figure that the size of the nanoparticles without doping with fluorescent molecules is about 2 nm, indicating that fluorescent molecules can effectively enhance the self-assembly degree of oligomers.
[0055] Figure 4 3D fluorescence spectrum of the oligomer in Example 1. It can be seen from the figure that the fluorescence emission of the oligomer without doping fluorescent molecules is mainly in the blue light region at 440nm.
[0056] Figure 53D fluorescence spectrum of the nanoparticles in Example 1. It can be seen from the figure that the fluorescence emission of the nanoparticles after doping with rhodamine B is red-shifted to about 600 nm.
[0057] Figure 6 The fluorescence spectra and photos of the supernatant and lower layer liquid after adding DMSO and dichloromethane in Example 1. It can be seen from the figure that the rhodamine B molecules can be effectively released by destroying the hydrogen bonds between polymer chains.
[0058] Example 2
[0059] 0.3 g of poly (N-ethyl-2-carboxymethylamide-succinimide) with an average molecular weight of 7000 Da was dissolved in 5 mL of ethanol at room temperature and stirred evenly. Subsequently, 120 mg of triacylglycerol was added and stirring was continued. Then, 4 mg of proflavin hydrochloride was added and stirring was continued. Finally, 50 mL of acetonitrile was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 78%.
[0060] Example 3
[0061] 0.2 g of poly (N-ethyl-2-carboxymethylamide)-succinimide with an average molecular weight of 7500 Da was dissolved in 3 mL of methanol at room temperature and stirred evenly. Then 4 mg of 7-diethylamino-4-methylcoumarin was added and stirring was continued. Then 30 mL of chloroform was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 65%.
[0062] Example 4
[0063] 0.3 g of polyphenyl oxalic acid diamide with an average molecular weight of 8000 Da was dissolved in 5 mL of acetonitrile at room temperature and stirred evenly. Subsequently, 100 mg of oxalic acid was added and stirring was continued. Then, 4 mg of rhodamine 6G was added and stirring was continued. Finally, 50 mL of toluene was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable, and the solid powder yield was 82%.
[0064] Example 5
[0065] 0.3 g of polyethyl oxalic acid diamide with an average molecular weight of 8000 Da was dissolved in 3 mL of acetone at room temperature and stirred evenly. Then 3 mg of 7-amino-2-methylquinoline was added and stirring was continued. Then 30 mL of n-hexane was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 78%.
[0066] Example 6
[0067] 0.3 g of polyethylene oxalic acid diimide with an average molecular weight of 8000 Da was dissolved in 3 mL of water at room temperature and stirred evenly. Then 2 mg of sodium fluorescein was added and stirring was continued. Then 30 mL of chloroform was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 76%.
[0068] Example 7
[0069] 0.3 g of polyphenylglutaramide with an average molecular weight of 7500 Da was dissolved in 3 mL of ethanol at room temperature and stirred evenly. Then 2 mg of Nile red was added and stirring was continued. Then 30 mL of chloroform was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 75%.
[0070] Example 8
[0071] 0.3 g of polyphenylglutaric acid diimide with an average molecular weight of 7500 Da was dissolved in 3 mL of acetonitrile at room temperature and stirred evenly. Then 4 mg of tris(2,2'-bipyridyldichlororuthenium(II)) was added and continued to stir. Then 30 mL of acetone was added. The precipitate was filtered and dried to obtain nanoparticles with adjustable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 79%.
[0072] Example 9
[0073] 0.3 g of poly(ethyl succinic acid diamide) with an average molecular weight of 8000 Da was dissolved in 5 mL of dimethyl sulfoxide at room temperature and stirred evenly. Then 4 mg of 1,3,5,7-tetramethyl-8-phenyl-4,4-difluorodiazepine was added and stirred continuously. Then 50 mL of ethanol was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 79%.
[0074] Example 10
[0075] 0.3 g of poly(ethyl succinic acid diimide) with an average molecular weight of 8000 Da was dissolved in 5 mL of dimethyl sulfoxide at room temperature and stirred evenly. Then 4 mg of anthraquinone was added and stirring was continued. Then 30 mL of n-hexane was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 82%.
[0076] Embodiment 11
[0077] 0.3 g of polyphenyl succinic acid diamide with an average molecular weight of 8000 Da was dissolved in 5 mL of water at room temperature and stirred evenly. Then 4 mg of fluorescein was added and stirring was continued. Then 30 mL of acetonitrile was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 76%.
[0078] Example 12
[0079] 0.3 g of polyphenyl succinic acid diimide with an average molecular weight of 7500 Da was dissolved in 5 mL of water at room temperature and stirred evenly. Then 4 mg of coumarin was added and stirring was continued. Then 30 mL of acetonitrile was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 78%.
[0080] Example 13
[0081] 0.3 g of polyethylglutaric acid diamide with an average molecular weight of 7500 Da was dissolved in 5 mL of methanol at room temperature and stirred evenly. Subsequently, 100 mg of glutaric acid was added and stirring was continued. Then, 4 mg of rhodamine 110 was stirred continuously. Finally, 50 mL of chloroform was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 84%.
[0082] Embodiment 14
[0083] 0.3 g of poly(ethylglutaric acid diimide) with an average molecular weight of 8000 Da was dissolved in 3 mL of dimethyl sulfoxide at room temperature and stirred evenly. Subsequently, 120 mg of ethylenediamine was added and stirring was continued. Then, 4 mg of Nile blue was added and stirring was continued. Finally, 50 mL of ethanol was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable. The solid powder yield was 76%.
[0084] Embodiment 15
[0085] 0.3 g of polyphenyl oxalic acid diimide with an average molecular weight of 8000 Da was dissolved in 3 mL of methanol at room temperature and stirred evenly. Subsequently, 100 mg of diaminobenzene was added and stirring was continued. Then, 4 mg of 7-amino-2-methylquinoline red was added and stirring was continued. Finally, 50 mL of acetonitrile was added. The precipitate was filtered and dried to obtain nanoparticles with controllable intraparticle fluorescence energy resonance transfer and energy receptor releasable, and the solid powder yield was 68%.
[0086] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing fluorescent nanoparticles, characterized in that: The following steps are involved: The mixed solution containing the non-conjugated polymer, the fluorescent molecule and the solvent I is mixed with the solvent II to obtain the fluorescent nanoparticles.
2. The preparation method according to claim 1, characterized in that: The molecular weight of the non-conjugated polymer is 7000-15000Da; The end-capping group of the non-conjugated polymer is a carboxyl group; The non-conjugated polymer contains pendant carboxyl groups; The non-conjugated polymer is obtained by the following method: Mixing polycarboxylic acid and polyamine, reacting, and drying to obtain the non-conjugated dehydrated polymer; The polycarboxylic acid is selected from at least one of oxalic acid, trisaccharic acid, succinic acid, 1,2,4-butanetricarboxylic acid, 1,2,3,4-butanetetracarboxylic acid, glutaric acid, adipic acid, and 1,2,4,5-cyclohexanetetracarboxylic acid; The polyamine is selected from at least one of ethylenediamine, propanetriamine, 1,3-propylenediamine and phenylenediamine; The reaction temperature is 80-260°C; The reaction atmosphere is an inert gas atmosphere. The molar ratio of the polycarboxylic acid to the polyamine is 1:10 to 10:1; The reaction is a melt polymerization reaction; The reaction time is 0.5 to 6 hours; The inert gas atmosphere is selected from at least one of nitrogen, helium and argon.
3. The preparation method according to claim 1, characterized in that: The fluorescent molecule is selected from at least one of fluorescein, rhodamine B, coumarin, platinum (II) MESO-tetrakis (pentafluorobenzene), proflavin hydrochloride, Nile red, (T-4)-[3-bromo-5-[(4-bromo-3,5-dimethyl-2H-pyrrole-2-ylidene-κN)benzyl]-2,4-dimethyl-1H-pyrrolidone-κN]difluoroboron (bromofluoroboron dipyrrole), cy3, terpyridine ruthenium chloride, 9,10-anthraquinone, and 2-methyl-7-quinolinamine; The solvent I is selected from at least one of DMSO, methanol, ethanol, water, acetonitrile and acetone; The mass ratio of the non-conjugated polymer to the fluorescent molecule is 1:0.01-1.
4. The preparation method according to claim 1, characterized in that: The mixed solution also contains monomers; The monomer is selected from at least one of oxalic acid, trisaccharic acid, succinic acid, glutaric acid, ethylenediamine, and diaminobenzene; The mass ratio of the non-conjugated polymer to the monomer is 1:0.01-10.
5. The preparation method according to claim 1, characterized in that: The solvent II is selected from at least one of ethanol, chloroform, acetone, acetonitrile, toluene and n-hexane; The volume ratio of the mixed solution to the solvent II is 0.1 to 1:
10.
6. Fluorescent nanoparticles prepared by the method for preparing fluorescent nanoparticles according to any one of claims 1 to 5.